2018
DOI: 10.1016/j.omtn.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Priming Human Repopulating Hematopoietic Stem and Progenitor Cells for Cas9/sgRNA Gene Targeting

Abstract: Engineered nuclease-mediated gene targeting through homologous recombination (HR) in hematopoietic stem and progenitor cells (HSPCs) has the potential to treat a variety of genetic hematologic and immunologic disorders. Here, we identify critical parameters to reproducibly achieve high frequencies of RNA-guided (single-guide RNA [sgRNA]; CRISPR)-Cas9 nuclease (Cas9/sgRNA) and rAAV6-mediated HR at the β-globin (HBB) locus in HSPCs. We identified that by transducing HSPCs with rAAV6 post-electroporation, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 56 publications
12
108
0
Order By: Relevance
“…Using the optimal template, our correction sequence was observed in 43  5% alleles ( Figure 1B) and INDELs were observed in 38  2% of the alleles ( Figure 1B), a ratio of HR:INDEL of >1 which is consistent with prior work that when optimal amounts of donor are delivered to dividing cells, high frequencies of HR-mediated editing are possible (Charlesworth et al, 2018;Hendel et al, 2014). On the day of extraction, 67  8% of edited cells were KRT5+ and Integrin Alpha-6+ (ITGA6+) which was similar to control (mock) cells, with 60  15% ( Figure 1C-D).…”
Section: Insertion Of Correction Sequence By Homologous Recombinationsupporting
confidence: 89%
See 2 more Smart Citations
“…Using the optimal template, our correction sequence was observed in 43  5% alleles ( Figure 1B) and INDELs were observed in 38  2% of the alleles ( Figure 1B), a ratio of HR:INDEL of >1 which is consistent with prior work that when optimal amounts of donor are delivered to dividing cells, high frequencies of HR-mediated editing are possible (Charlesworth et al, 2018;Hendel et al, 2014). On the day of extraction, 67  8% of edited cells were KRT5+ and Integrin Alpha-6+ (ITGA6+) which was similar to control (mock) cells, with 60  15% ( Figure 1C-D).…”
Section: Insertion Of Correction Sequence By Homologous Recombinationsupporting
confidence: 89%
“…Isolation and culture of UABCs: Cas9-based gene editing utilizing the homologous recombination pathway to correct mutations has been shown to be improved under conditions that promote cell proliferation (Charlesworth et al, 2018). Therefore, we first optimized cell culture conditions to both increase proliferation of basal cells and improve their survival after electroporation (also called nucleofection).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it has been reported that the HR rates can be dramatically boosted by simply altering the cell culture density of CD34 + HSPCs in order to promote cell cycling, which is thought to be necessary for efficient HR. 51 Therefore, it would be of great interest to perform additional tran-scriptional analysis on HSPCs that have been targeted using the HR-optimized protocol.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that, in autosomal recessive haematological disorders, even the genome-editing-mediated correction of only one of the two affected alleles in a reasonably high proportion of haematopoietic stem cells (HSCs) would avoid the need for multiple copies of the integrated lentiviral vector with suboptimal transgene expression. Although HDR-based approaches for correcting haematological genetic disorders are relatively efficient in haematopoietic stem and progenitor cells (HSPCs), the frequency of stably modified, repopulating HSCs rarely exceeds 10% [149][150][151][152][153][154][155] , suggesting that stem cells might be poorly permissive to HDR (which is typical of nonquiescent cells). The inclusion of selectable markers in the donor template enables the enrichment of edited HSCs 151 ; however, cell selection would be difficult to translate into the clinic because it would yield lower numbers of HSCs than conventional approaches do.…”
Section: Gammaretroviruses the Most Extreme Examples Of Cell Prolifementioning
confidence: 99%